Catalogue of the type-specimens of Bolitophilidae, Diadocidiidae and Ditomyiidae (Diptera, Bibionomorpha) in the Natural History Museum, London - Rafaela Lopes Falaschi; Dalton de Souza Amorim (Revista Brasileira de Entomologia, 2013)
Catalogue of the type-specimens of Bolitophilidae, Diadocidiidae and Ditomyiidae (Diptera, Bibionomorpha) in the Natural History Museum, London. A commented list of the types of three families of Bibionomorpha - Bolitophilidae, Diadocidiidae and Ditomyiidae - housed at the Natural History Museum (London) is provided. This includes four holotypes and one paratype of five species of Bolitophilidae; one paratype and three syntypes of two species of Diadocidiidae; and 17 holotypes, 91 paratypes, four lectotypes, and fourteen paralectotypes of 38 species of Ditomyiidae. Lectotypes are designated for the Neotropical species of the ditomyiids Australosymmerus (Melosymmerus) bisetosus Edwards, 1940 and A. (M.) pediferus Edwards, 1940.